Pengaruh Profitabilitas, Perencanaan Perpajakan, dan Solvabilitas Terhadap Manajemen Laba Pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar Di Bursa Efek Indonesia Periode 2022-2024 - JulietaAnta Maulani; Untung Wahyudi; Dwi Anggarani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine the influence of profitability, tax planning, and solvency on earnings management in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. Profitability is assessed through return on assets (ROA), tax planning through the effective tax rate (ETR), and solvency through the debt-to-assets ratio (DAR). Earnings management is evaluated using a modified Jones discretionary accrual accounting approach. The method used in this study is quantitative with multiple linear regression. Sample selection was carried out by applying certain criteria, resulting in a number of companies that met the research requirements. Secondary data was taken from annual financial reports accessible on the official IDX website. It is hoped that the results of this study will provide empirical evidence regarding the relationship between these three independent variables and earnings management and contribute to the development of the accounting and finance literature, particularly in the context of managerial decision-making and corporate policy-making in the transportation and logistics sector. Keywords: Earning Management,Profitability, Tax Planning, Solvency